PENGARUH KUALITAS PELAYANAN DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN â€œXLâ€ - Muhammad Yudha Gozali; Ian Nurpatria Suryawan (Jurnal Ekonomi Perusahaan, 2016)
Mobile phone is a very important need this day, many operators who offer different promos, resulting in a price war. Loyalty is very important because the search for new customers will provide a cost more expensive than maintaining existing ones. The objective of this research is to analyze the impact of service quality as independent variable (X1) and satisfaction as independent variable (X2) to customer loyalty as dependent variable (Y) on customer that used XL service provider in the faculty of economics, Tarumanagara University. This study is race from the research conducted by Satouridis and Trivellas, (2010). The sample of this research is 50 respondents, after processing the data, is known that service quality (X1) and satisfaction (X2) have a significant effect on customer loyalty. Keyword : service quality, satisfaction, loyalty